Mechanisms and Drivers for the Establishment of Life Cycle Complexity in Myxozoan Parasites - Lisnerová, Martina; Fiala, Ivan; Cantatore, Delfina; Irigoitia, Manuel; Timi, Juan; Pecková, Hana; Bartošová-Sojková, Pavla; Sandoval, Christian M; Luer, Carl; Morris, Jack; Holzer, Astrid S (Biology, 2020)
It is assumed that complex life cycles in cnidarian parasites belonging to the Myxozoa result from incorporation of vertebrates into simple life cycles exploiting aquatic invertebrates. However, nothing is known about the driving forces and implementation of this event, though it fostered massive diversification. We performed a comprehensive search for myxozoans in evolutionary ancient fishes (Chondrichthyes), and more than doubled existing 18S rDNA sequence data, discovering seven independent phylogenetic lineages. We performed cophylogenetic and character mapping methods in the largest monophyletic dataset and demonstrate that host and parasite phylogenies are strongly correlated, and that tectonic changes may explain phylogeographic clustering in recent skates and softnose skates, in the Atlantic. The most basal lineages of myxozoans inhabit the bile of chondrichthyans, an immunologically privileged site and protective niche, easily accessible from the gut via the bile duct. We hypothesize that feed-integration is a likely mechanism of host acquisition, an idea supported by feeding habits of chimaeras and ancient sharks and by multiple entries of different parasite lineages from invertebrates into the new host group. We provide exciting first insights into the early evolutionary history of ancient metazoan parasites in a host group that embodies more evolutionary distinctiveness than most other vertebrates.
Keywords: feed-integration; migration; myxozoa; co-phylogeny; phylogeography; Chondrichthyes; cnidaria; co-diversification